2019
DOI: 10.1002/ccd.28228
|View full text |Cite
|
Sign up to set email alerts
|

Impact of strut thickness and number of crown and connectors on clinical outcomes on patients treated with second‐generation drug eluting stent

Abstract: Introduction: In new generation drug eluting stents (DESs) era, the impact of stent geometry on freedom from recurrent events has been poorly explored. Impact of struts thickness and the number of crowns and connectors on clinical outcomes were evaluated in the present study. Methods: Randomized controlled trials comparing last generation DESs were selected. The primary endpoint was the rate of target lesion revascularization (TLR), while secondary was definite stent thrombosis (ST). Results: Fifty-three studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…DP-DES are equally heterogeneous groups. Innaccone et al observed that lower strut thickness would have a positive clinical outcome, thereby reducing ST and TLRs 37. We were unable to match the stents with regards to the strut thickness.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…DP-DES are equally heterogeneous groups. Innaccone et al observed that lower strut thickness would have a positive clinical outcome, thereby reducing ST and TLRs 37. We were unable to match the stents with regards to the strut thickness.…”
Section: Discussionmentioning
confidence: 89%
“…Innaccone et al observed that lower strut thickness would have a positive clinical outcome, thereby reducing ST and TLRs. 37 We were unable to match the stents with regards to the strut thickness. Consequently, the reported results may not be generalisable to all stents from the respective group.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of strut thickness on subsequent repeat revascularization remains inconclusive in the literature. A recent meta‐analysis of RCTs focusing on new DESs reported that the incidence of 1‐year TLR favored DESs with strut thickness ≤ 81 μm when compared with those > 81 μm 14 . Conversely, a network meta‐analysis investigating both early and new DESs reported that TLR incidence was comparable among DESs with struts of 60–80, 81–100, 101–120, and > 120 μm 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Strut thickness and TLRThe impact of strut thickness on subsequent repeat revascularization remains inconclusive in the literature. A recent meta-analysis of RCTs focusing on new DESs reported that the incidence of 1-year TLR favored DESs with strut thickness ≤ 81 μm when compared with those > 81 μm 14. Conversely, a network meta-analysis investigatingF I G U R E 2Scatterplots of event incidence against stent strut thickness at study-arm level along with meta-regression lines, regarding early stent thrombosis (EST; A), late stent thrombosis (LST; B), and 5-year very late stent thrombosis (VLST; C).…”
mentioning
confidence: 99%
“…Joner et al (2006) reported this delayed arterial healing with drug‐eluting stents as part of a study to investigate the long‐term effects of stents on coronary arterial healing. The current standard of care in revascularization, the second‐generation drug‐eluting stent was introduced with ultrathin struts (80–90 µm), reduced drug loading and more biocompatible or biodegradable polymers (Bangalore, Toklu, Patel, Feit, & Stone, 2018; Beijk & Piek, 2007; Iannaccone et al, 2019; Palmerini et al, 2013). Nevertheless, the presence of antiproliferative drug and polymers can adversely elicit delayed or incomplete endothelialization obviating the need for a prolonged dual antiplatelet therapy (DAPT) (Bønaa et al, 2016; McFadyen, Schaff, & Peter, 2018).…”
Section: Introductionmentioning
confidence: 99%